3D Hyperbranched Hollow Carbon Nanorod Architectures for High‐Performance Lithium‐Sulfur Batteries. Issue 8 (29th January 2014) - Chen, Shuangqiang; Huang, Xiaodan; Liu, Hao; Sun, Bing; Yeoh, Waikong; Li, Kefei; Zhang, Jinqiang; Wang, Guoxiu
<x xml:space="preserve">Abstract</x> Lithium‐sulfur batteries have been plagued for a long time by low Coulombic efficiency, fast capacity loss, and poor high rate performance. Here, the synthesis of 3D hyperbranched hollow carbon nanorod encapsulated sulfur nanocomposites as cathode materials for lithium‐sulfur batteries is reported. The sulfur nanocomposite cathodes deliver a high specific capacity of 1378 mAh g‐1 at a 0.1C current rate and exhibit stable cycling performance. The as‐prepared sulfur nanocomposites also achieve excellent high rate capacities and cyclability, such as 990 mAh g‐1 at 1C, 861 mAh g‐1 at 5C, and 663 mAh g‐1 at 10C, extending to more than 500 cycles. The superior electrochemical performance are ascribed to the unique 3D hyperbranched hollow carbon nanorod architectures and high length/radius aspect ratio of the carbon nanorods, which can effectively prevent the dissolution of polysulfides, decrease self‐discharge, and confine the volume expansion on cycling. High capacity, excellent high‐rate performance, and long cycle life render the as‐developed sulfur/carbon nanorod nanocomposites a promising cathode material for lithium‐sulfur batteries.